Risk Analysis of Toll Road Accident Using Fmea and Ahp Methods - Haryanto, Edelweis Gent; Latifa, Eva Azhra (POLITEKNIK NEGERI JAKARTA, 2020)
Road accidents are one of the leading causes of death in the world. It is not only the victims that killed or seriously injured, but accidents significantly affected the quality of life of the people as well as economic and social development in the country. However, the threat of road accidents has not been fully recognized, and has not been well studied even though it is one of the most frequent causes of human death and loss of property. This research was conducted to determine the causes of accidents on the toll road with the FMEA method (Failure Mode Effect Analysis) which is divided into 3 factors: human factors, vehicle factors, and road factors. After that, determining the alternative solutions for dealing with accidents on toll roads using the Analytical Hierarchy Process based on 3 criteria: cost, time and impact. The results showed that based on FMEA analysis, the highest risk factors were found to be human factors caused by negligence. Based on risk factors due to negligence, the results of AHP analysis are: the impact criteria as the main criteria with a weight value of 0.77, and the chosen alternative solution is the fulfillment of functional feasibility with global weight 0.42. Fulfillment of functional feasibility can be done by adding road equipment such as traffic signs and rumble stripe markers.